Efficacy of Eladi Yoga Kwatha in the Management of Renal Calculi (International Journal of Ayurveda and Pharma Research, 2025)
Renal calculi are one of the most common diseases of the urinary tract. Renal stones are hard deposits of minerals and acid salts that stick together in concentrated urine. It is rare in children and shows a familial predisposition. Treatment of renal calculi depends upon the size and symptoms of the disease along with the site of renal calculi. Modern management includes invasive and non-invasive procedures which are either expensive or with side effects. Ayurveda has given a proper and detailed description on Asmari explaining its Nidana and there are various formulations mentioned in Ayurvedic classical texts having Asmari bhedaka (disintegration of calculi) property which alleviates the aggravated doshas and brings to normalcy with no complications. Eladi yoga kwatha is one such formulation mentioned in Asmari chikitsa of Haritha samhitha with Eranda thaila, and Shilajathu as Anupana having Mutrala and Asmarigna properties. This case report details the clinical presentation and management of a 60-year-old male patient presented with pain over renal angle and was diagnosed with renal calculi in USG for 2 years. The patient was given Eladi yoga kwatha in the dosage of 48ml with Shilajathu and Eranda thailam twice daily before food for 30 days. The assessment was done periodically was analysed using appropriate statistical tests before and after the treatment. Post USG (abdomen and pelvis) revealed a significant reduction in the size of Renal calculi. Hence it is proven that an Ayurveda formulation offers an effective option in the management of renal calculi.